2009
DOI: 10.1152/ajpregu.00236.2009
|View full text |Cite
|
Sign up to set email alerts
|

Functional overload in ground squirrel plantaris muscle fails to induce myosin isoform shifts

Abstract: We performed 2 wk of mechanical overload by synergist ablation on plantaris muscles from a small rodent hibernator, Spermophilus lateralis. While this muscle displays prominent myosin heavy-chain (MyHC) isoform shifts during hibernation, sensitivity to mechanical loading as a stimulus for muscle mass and isoform plasticity has not been demonstrated. Squirrel muscles, whether during hibernation or not, potentially are less sensitive to mechanical unloading, but we hypothesized that increased loading would produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 93 publications
1
27
0
Order By: Relevance
“…Tenotomy has the disadvantage of the rapid reconnection of the cut tendon, which limits functionality. 65 Most commonly studied muscles Compensatory hypertrophy by the ablation of synergists is an efficient model for studies on muscle hypertrophy, 2,3,7,[10][11][12][13][14][15][16][17][18][19][20] as the fast increase in muscle mass reduces the duration of the experiment. In recent years, changes have occurred in the standard of surgery (bilateral or unilateral) and the relationship between the number of days and increase in muscle mass, which justifies this systematic review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tenotomy has the disadvantage of the rapid reconnection of the cut tendon, which limits functionality. 65 Most commonly studied muscles Compensatory hypertrophy by the ablation of synergists is an efficient model for studies on muscle hypertrophy, 2,3,7,[10][11][12][13][14][15][16][17][18][19][20] as the fast increase in muscle mass reduces the duration of the experiment. In recent years, changes have occurred in the standard of surgery (bilateral or unilateral) and the relationship between the number of days and increase in muscle mass, which justifies this systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,7,[10][11][12][13][14][15][16][17][18][19][20] The most studied muscles are plantar flexors in the rear paw of rats. As skeletal muscle has different types of fibers (type I [slow--twitch] and type II [fast-twitch -IIa, IIb, IIx/IId]), 21 a number of authors justify the choice of the plantaris muscle due to its diversity of fiber types (type I: 8 ± 2%; type IIA: 19 ± 3%; type IIB/D: 74 ± 4%) and its different adaptation possibilities.…”
mentioning
confidence: 99%
“…Exercise and training have also been associated with decreased expression of myostatin mRNA and protein in humans (Roth et al, 2003;Raue et al, 2006;Louis et al, 2007) and rats (Matsakas et al, 2005;Matsakas et al, 2006;Heinemeier et al, 2007), although this finding has not been consistent. In response to overloading of the plantaris muscle in ground squirrels (Callospermophilus lateralis), muscle hypertrophy was observed without a change in the expression of myostatin mRNA (Choi et al, 2009). In other mammalian studies, muscle myostatin expression has paradoxically increased in response to training or overloading in skeletal or cardiac muscle (Sakuma et al, 2000;Willoughby, 2004;Matsakas et al, 2006;Jensky et al, 2007;Jensky et al, 2010).…”
Section: Exercise and The Expression Of Myostatin Tll1 And Igf1 Mrnamentioning
confidence: 97%
“…Previous work in mammals has demonstrated that IGF1 expression in muscles is induced by muscle contraction and during compensatory hypertrophy (DeVol et al, 1990;Heinemeier et al, 2007;Choi et al, 2009). IGF1 is known to stimulate protein synthesis in myocytes and also satellite cell proliferation, leading to hypertrophy (Rennie et al, 2004).…”
Section: Exercise and The Expression Of Myostatin Tll1 And Igf1 Mrnamentioning
confidence: 99%
See 1 more Smart Citation